Pengembangan Film Kartun Sebagai Media Pembelajaran Tematik Siswa Kelas IV SDN 9 Sampurtoba, Kec. Harian - Robenhart Tamba; Rohayati Sihotang (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2023)
This research is a development research (R&D) using the ADDIE development model which consists of: 1.) Analysis; 2.) Design; 3.) Development; 4.) Implementation; and 5.) Evaluation. Data collection was carried out by interviews, questionnaires and tests. The results of the interviews were analyzed descriptively qualitatively, while questionnaires and tests were analyzed quantitatively. Validation was carried out by questionnaire instrument experts, material experts, media experts and practitioner experts by class IV educators. The results of the analysis show that cartoon film learning media is included in the "very feasible" category to be used as a learning medium in class IV SDN 9 Sampurtoba. Based on Validation: 1.) Questionnaire Instrument Expert with an average percentage of 90%; 2.) Learning material experts get an average percentage of 95%; 3.) Learning media experts with an average percentage of 95%; 4.) Expert Practitioner with an average percentage of 93%. And continued with the distribution of Pre-Test and Post-Test questions to class IV with a lot of 15 students, obtained an average Pre-Test score of 42 increased with an average post-test result of 80. From the data acquisition it can be concluded that the developed cartoon film learning media is effective in improving learning outcomes.